An Overview of Current Alternative Models for Use in the Context of Prostate Cancer Research. Issue 2 (March 2020) - Nascimento-Gonçalves, Elisabete; Ferreira, Rita; Oliveira, Paula A.; Colaço, Bruno Jorge Antunes
Prostate cancer is one of the most commonly diagnosed cancers worldwide, particularly in elderly populations. To mitigate the expected increase in prostate cancer-related morbidity and mortality as a result of an expanding aged population, safer and more effective therapeutics are required. To this end, plenty of research is focusing on the mechanisms underlying cancer initiation and development, the metastatic process and on the discovery of new therapies. While animal models are used (mainly rats and mice) for the study of prostate cancer, alternative models and methods are increasingly being considered to replace, or at least reduce, the number of animals used in this particular field of research. In this review, we cover some of the alternative models that are currently available for use in the study of prostate cancer, including: mathematical models; 2-D and 3-D cell cultures; microfluidic devices; the chicken egg chorioallantoic membrane-based model; and zebrafish embryo-based models. The main advantages and limitations, as well as some examples of applications, are given for each type of model. According to our analysis, immortalised cell lines are still the most commonly used models in the field of prostate cancer research. However, the use of alternative models for prostate cancer research will likely become more prevalent in the coming years partly because of the increasing societal pressure to reduce the numbers of laboratory animals. In this context, the development and dissemination of effective non-animal alternative models assumes particular relevance and will be instrumental in leveraging their success. Taking these perspectives into account, we believe that technological advances will lead to more effective cell culture systems, namely 3-D cultures or organ-on-a-chip devices, which can be used to replace animal-based models in prostate cancer research.